NGHIÊN CỨU CHIẾT PHLOROTANNIN VỚI HOẠT TÍNH CHỐNG OXY HÓA TỪ RONG NÂU Sargassum mcclurei BẰNG PHƯƠNG PHÁP NGÂM DẦM CÓ HỖ TRỢ VI SÓNG - Dang, Cuong Xuan; Thanh Vân, Trần Thị; Bội, Vũ Ngọc; Lý, Bùi Minh (Vietnam Journal of Science and Technology, 2014)
The extraction condition for phlorotannin with antioxidant activity from brown algae Sargassum mcclurei was focused to research in the paper. Microwave-assisted maceration method with the 100% ethanol 960 extraction solvent was used to research. Phlorotannin content with total antioxidant activity and reducing power activity were evaluated. Some factors of extraction step ( microwave power: 100 – 800W; the ratio of solvent-material from 10:1 to 50:1 (w/w); time: 1 – 5 minutes; pH 5 – 9 and times) were researched. The result showed that the fit extraction condition was as follow: the microwave power of 100W, the solvent-material ratio of 30:1 (v/w), the time of 2 minutes, pH of 7 and the 3 times). At this fit extraction condition, phlorotannin content with total antioxidant activity and reducing power activity were corresponded with 3,88 ± 0,033 mg phloroglucinol/g DW, 15,096 ± 0,037 mg acid ascorbi/g DW and 5,365 ± 0,028 mg FeSO4/ g DW. ANOVA analysis showed that the object functions were correlated each other follow the non-linear function.